Determinants of length of stay in the psychiatric wards of the University College Hospital, Ibadan, Nigeria (2012)
Background: Inpatient care constitutes the most expensive component of psychiatric services and pressure is increasingly being mounted on clinicians to discharge patients early. With the advent of managed care in Nigeria, psychiatrists as well as other physicians will be faced with the challenge of having to justify patient’s length of hospital admission. This study was designed to examine the factors that influence the length of stay (LOS) in an acute psychiatric ward. Methods'. A list of all patients admitted to the psychiatric unit of the UCH for the twelve month period between June 1st 2006 and May 31st 2007 was compiled from the ward admission registers. Data were extracted from the patient’s case notes using specially designed data record forms. Results: There were a total of three hundred and seventy one (371) admissions made up of three hundred and thirty three (333) patients, out of which a total of 247 (74.5%) case notes were successfully reviewed. The most common diagnoses necessitating admission were schizophrenia and mood disorders. The mean LOS was 28.7 days and bed turnover for this period was 5.8. Factors found to be significantly associated with longer LOS include age, diagnosis, previous admissions and receiving electroconvulsive therapy with medication. These factors need to be considered in determining the period of hospitalization covered under managed care schemes.